2018
DOI: 10.1080/0284186x.2018.1479068
|View full text |Cite
|
Sign up to set email alerts
|

First fully automated planning solution for robotic radiosurgery – comparison with automatically planned volumetric arc therapy for prostate cancer

Abstract: The first system for fully automated generation of clinically deliverable robotic plans was built. Autoplanning did largely enhance robotic plan quality, compared to manual planning. Using autoplanning for both the robotic system and VMAT, superiority of non-coplanar robotic treatment compared to coplanar VMAT for prostate SBRT was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 46 publications
3
37
0
Order By: Relevance
“…The investigated MRL system only allows coplanar treatment. In previous studies using automated planning we observed superiority of non-coplanar treatment compared to coplanar [23]. However, in [23] equal PTV margins were used for the coplanar and non-coplanar plans.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The investigated MRL system only allows coplanar treatment. In previous studies using automated planning we observed superiority of non-coplanar treatment compared to coplanar [23]. However, in [23] equal PTV margins were used for the coplanar and non-coplanar plans.…”
Section: Discussionmentioning
confidence: 83%
“…In previous studies using automated planning we observed superiority of non-coplanar treatment compared to coplanar [23]. However, in [23] equal PTV margins were used for the coplanar and non-coplanar plans. Due to the advanced imaging, it is to be expected that margins can be largely reduced for the MRL.…”
Section: Discussionmentioning
confidence: 83%
“…The radiation beams can be precisely directed toward the targeted tumors while avoiding healthy tissues. [361] This approach does not require any physical interaction between the surgical devices and patient during the operation. A few commercial systems such as the CyberKnife, the Novalis, and the Gamma Knife have successfully used automation in surgery.…”
Section: Potential Surgeries With Automationmentioning
confidence: 99%
“…There is a concern that reducing the input of humans into radiotherapy processes could lead to a more blas e approach and reduction in the effects of curiosity and invention. An example of this is a recent article investigating a robotic radiosurgery autoplanning system [9] that compared outcomes with another autoplanning system, completely eliminating the human solution. With many of the current AI and machine learning articles relegating humans to the role of oversight and checking, this does seem like a possible consequence.…”
Section: Innovation In Radiotherapymentioning
confidence: 99%